2016
DOI: 10.4269/ajtmh.15-0361
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Cytokines and Chemokines Triggered by Wild-Type Strains of Rabies Virus in Mice

Abstract: Abstract. Rabies is a lethal infectious disease that causes 55,000 human deaths per year and is transmitted by various mammalian species, such as dogs and bats. The host immune response is essential for avoiding viral progression and promoting viral clearance. Cytokines and chemokines are crucial in the development of an immediate antiviral response; the rabies virus (RABV) attempts to evade this immune response. The virus's capacity for evasion is correlated with its pathogenicity and the host's inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…They observed altered gene expression at days 2 (29 genes), 4 (109 genes) and 6 (98 genes) post-inoculation in eight major groups: immune response, metabolism, receptor and transport, growth factors, death-mediated factors, transcription and translation factors, proteases and kinases. The up-regulation of VCAM-1 in the present study demonstrates the participation of this molecule in viral penetration, in which the activation occurred immediately after entry of the virus in the brain and in the absence of clinical signs, corroborating previous works published by our group and others [9,[15][16][17].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…They observed altered gene expression at days 2 (29 genes), 4 (109 genes) and 6 (98 genes) post-inoculation in eight major groups: immune response, metabolism, receptor and transport, growth factors, death-mediated factors, transcription and translation factors, proteases and kinases. The up-regulation of VCAM-1 in the present study demonstrates the participation of this molecule in viral penetration, in which the activation occurred immediately after entry of the virus in the brain and in the absence of clinical signs, corroborating previous works published by our group and others [9,[15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…The V2 RABV variant was more lethal thanV3, in agreement with previous studies [9][10][11][12]. Fuoco et al (2019) showed that intradermal inoculation of mice with a RABV isolate from an insectivorous bat led to 33% mortality whereas an isolate from a wild canid (Cerdocyon thous, crab-eating fox) led to 67% mortality [13].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The presence of these cytokines initiate a cascade reaction, upregulating proteins necessary for the inflammatory response such as the major histocompatibility complex and adhesion molecules. These proteins then interact with leukocytes to allow the blood brain barrier to become more permeable, thus causing an immune response leading to encephalitis [30]. As for the natural defense against rabies, RABV signals a series of molecular cascades that initiates type I interferon responses that have antiviral properties, decreasing the pathogenicity of rabies [31].…”
Section: Clinical Course 31 Pathophysiologymentioning
confidence: 99%